Anti-VEGF therapy induces ECM remodeling and mechanical barriers to therapy in colorectal cancer liver metastases - Rahbari, Nuh N. (Sci Transl Med, 2016)
The survival benefit of anti–vascular endothelial growth factor (VEGF) therapy in metastatic colorectal cancer (mCRC) patients is limited to a few months because of acquired resistance. We show that anti-VEGF therapy induced remodeling of the extracellular matrix with subsequent alteration of the physical properties of colorectal liver metastases. Preoperative treatment with bevacizumab in patients with colorectal liver metastases increased hyaluronic acid (HA) deposition within the tumors. Moreover, in two syngeneic mouse models of CRC metastasis in the liver, we show that anti-VEGF therapy markedly increased the expression of HA and sulfated glycosaminoglycans (sGAGs), without significantly changing collagen deposition. The density of these matrix components correlated with increased tumor stiffness after anti-VEGF therapy. Treatment-induced tumor hypoxia appeared to be the driving force for the remodeling of the extracellular matrix. In preclinical models, we show that enzymatic depletion of HA partially rescued the compromised perfusion in liver mCRCs after anti-VEGF therapy and prolonged survival in combination with anti-VEGF therapy and chemotherapy. These findings suggest that extracellular matrix components such as HA could be a potential therapeutic target for reducing physical barriers to systemic treatments in patients with mCRC who receive anti-VEGF therapy.